Analyzing the critical success factor of CSR for the Chinese textile industry - Li, Yongbo (2020)
Increasing population and urbanization motivates the capability of consuming more fashion goods than ever. This push creates more momentum on global companies to focus on clothing sectors. Recent advancements, including globalization and e-commerce, have made this sector as one of the top businesses worldwide. Top clothing brands made several strategies to satisfy the stakeholders to sustain in this hot, profitable business. This results in practicing more sustainable strategies, including corporate social responsibility in their clothing business throughout their operations, including the supply chain. However, most of the developed nations are consumers of textiles, which are produced and processed by any of the developing and under developing nations. Meanwhile, achieving sustainability in clothing business includes promoting sustainability in the whole chain of suppliers. Pressure from developed nations urges developing nations to promote sustainable practices in their operations. Several studies discussed the CSR related strategies in textile sectors but failed to explore their critical success factors based on their region. With this concern, this study attempts to study the critical success factors of CSR in textile industries situated in one of the developing nations, China. This study collected the critical success factors from literature and validated with the field experts; then the same were evaluated with the assistance of Chinese textile case industrial managers. Decision-making trial and evaluation laboratory tool has been used to evaluate the influential critical success factors of CSR to promote CSR through motivating those most influential success factors. These results could help the Chinese textile industrial managers to further extend strong roots on CSR implementation. Finally, this study sheds some light on future opportunities that exist within Chinese contexts with the implementation of CSR.